Upregulation of exosomal circPLK1 promotes the development of non-small cell lung cancer through the miR-1294/ high mobility group protein A1 axis. Issue 2 (1st February 2022) - Li, Chuankui; Wang, Guowen; Ma, Xiaoxiao; Tao, Tao; Li, Qicai; Yang, Yifan; Sang, Haiwei; Wang, Zuyi
ABSTRACT: CircRNAs (circular RNAs) have been implicated in the development and progression of a variety of cancers. The molecular pathways underlying the progression of NSCLC (Non-Small Cell Lung Cancer) and the associated regulation of circRNAs in NSCLC remain to be fully elucidated. In this study, we found that circPLK1 expression was upregulated in serum exosomes and tissues from NSCLC patients. The Kaplan–Meier survival analysis revealed that a high expression level of circPLK1 was associated with a poorer prognosis in NSCLC patients. Exosomes extracted from NSCLC serum could promote the replication, migration, and invasion of NSCLC cells and suppress apoptotic cell death. The overexpression of circPLK1 also promotes the malignant phenotype of NSCLC cells. Molecular analyses demonstrated that circPLK1 directly targets miR-1294 and negatively regulates its activity. And circPLK1 overexpression facilitates the progression of NSCLC by negatively regulating miR-1294 level and maintaining a high-level expression of HMGA1 (High Mobility Group Protein A1). Our study suggests that circPLK1 upregulation plays an important role in NSCLC progression by targeting miR-1294/HMGA1 axis. These data provide a theoretical basis for the development of therapeutic strategy targeting exosomal circPLK1 in NSCLC treatment.